Design and evaluation of surveys and A/B tests - Dzhinchvelashvili, Vaso (2022)
This thesis reports on comparison of methodologies of designing and evaluation of tests, which include surveys, A/B tests, natural experiments, with a main focus on A/B tests. The aim is to compare different approaches, highlight advantages and limitations based on review of literature, pick the best suitable one and simultaneously test on real enterprise data. The outcome of the research could be used to contribute to a decision making in enterprise. The approaches to randomisation, feature selection are described as well.